PENGEMBANGAN TES KEMAMPUAN BERBAHASA JEPANG BERBASIS WEB - Desak Made Sri Mardani (Universitas Pendidikan Ganesha, 2018)
Japanese proficiency test with convenient access as part of technology growth is an urge of thisresearch. This research was conducted by adopting a Research and Development (R&D) method, usingthe lecturers and the students in Japanese Education Department - Universitas Pendidikan Ganesha -as the research subjects, while a web-based test was plotted as the research object. A web-based testwas concluded as the result of the requirement analysis phase, in order to facilitate administration ofgraduation standards. On the development phase, the web system was designed focused particularly onuser experience so end user could experience the system in a convenient way. Content experts declaredthat the tests have been created have a good quality. After conducting expert judgement, limited test (20grade-4 students) were held, as result, it has a very high point of both reliability level and user response.By empirical validity, some test-questions were recommended to be changed as they have high item difficultyand low item discrimination.Keywords: Nihongo Noryoku Shiken, web-based test, item difficulty, item discrimination